Отец Арсений: [сборник воспоминаний] (Библиотека духовной прозы, 2021)
Экземпляры: ЦБ/3 (20250227) / Инвентарный номер: 67724 / Цена: 300.00 / Сис.шифр: 86.37 / Авт.знак: О-82 / ГРНТИ: 21 / ББК: 86.37